Study on Optical Positioning Using Experimental Visible Light Communication System - Nikoleta Vitsi; Argyris N. Stassinakis; Nikolaos A. Androutsos; George D. Roumelas; George K. Varotsos; Konstantinos Aidinis; Hector E. Nistazakis (Computation, 2023)
Visible light positioning systems (VLP) have attracted significant commercial and research interest because of the many advantages they possess over other applications such as radio frequency (RF) positioning systems. In this work, an experimental configuration of an indoor VLP system based on the well-known Lambertian light emission, is investigated. The corresponding results are also presented, and show that the system retains high enough accuracy to be operational, even in cases of low transmitted power and high background noise.